New records of Scythrididae from Namibia, with descriptions of five new species (Lepidoptera: Scythrididae) - K. Nupponen; R. Haverinen; A. Pototski (SHILAP)
A list of 24 species embracing 1505 specimens of the family Scythrididae from Namibia is presented. The material was collected during November–December 2019 in the course of a Finnish–Estonian expedition to the Northern and Central Namibia. Five new species are described: Haploscythris fannyae Nupponen, sp. n., Scythris eburnipalpella Nupponen sp. n., S. eneae Nupponen, sp. n., S. fimbriatella Nupponen, sp. n., and S. pretarsella Nupponen, sp. n. Scythris curvipilella Bengtsson, 2002, S. mesoplecta Meyrick, 1921 and S. sericiella Bengtsson, 2014 are reported as new to Namibia. The known distribution range of each species is given.